PERFORMANCE OF VOCATIONAL EDUCATION IN LATVIA IN DEVELOPING EMPLOYABILITY OF GRADUATES - Lice, Anita; Sloka, Biruta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
As the labour market changes at increasing pace, education systems need to respond. Facilitating employability of graduates and preparing them for lifelog learning and constant changes throughout their careers requires new education methods. In order to assess the current approach to developing employability of graduates in vocational education in Latvia, this article aims at evaluating the attitudes of employers on performance of vocational education in developing employability competencies, as well as investigating the practical education methods applied by vocational education institutions to facilitate employability.Total 750 companies participated in this research. A list of 17 employability competencies was rated using a four-point Likert scale. Employers rated the relative performance of vocational education in developing employability competencies. In order to investigate  education methods applied to facilitate development of employability competencies, interviews with managers of 12 vocational education institutions were conducted. The research results show that vocational education in Latvia is best at developing computer skills and presentation skills, however it performs worst at developing the ability to take responsibility, ensuring relevant work experience, developing problem-solving skills and  appropriate attitude to work. Overall, performance of vocational education received almost as many negative evaluations as positive evaluations. The main education methods to facilitate employability of graduates used by vocational education institutions are practical learning and extra-curricular activities.